The Readability and Design of Health Education Materials - Fadime Hatice Inci; Nazan Koştu; Ilgün Özen-çinar; Gülbahar Korkmaz-aslan; Asiye Kartal (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Objective: The aim of the study was to assess readability and design of health education materials. Methods: This is a descriptive study. Thirty-seven education materials prepared by Denizli Provincial Directorate of Health and Turkish Republic Ministry of Health and used in primary health care services in Denizli were examined in this study. Flesch Reading Ease Score and Turkish Readability Value were used to evaluate readability of the health education materials. The design of health education materials were evaluated using a twenty-seven-item list developed by the researchers. Results: Mean Flesch Reading Ease score was 44.59±23.46, and mean Turkish Readability Value was 11.02±3.63. The results indicate that those health education materials are difficult to read. The design of the education materials, although the title, information, content, and language were superior, page layout, writing style, and figures were inappropriate. Conclusions: The readability levels were found higher than the level of sixth grade. Therefore, it is recommended that the health education materials should be reorganized for easier reading comprehension, and their organization and design as well as their readability should be evaluated for the sake of comprehensibility so that those materials can fulfill their purposes